NF-κB/RELA Knockout Reveals a Role in Expression of HIF-1α and NES in A172 Cell Line: Suggestion Ecteinascidin-743 as a Suitable Drug - Sima Salmani; Dhiya Altememy; Sepideh Parvizpoor; Akram Alizadeh; Sorayya Ghasemi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The NF-κB signalling pathway is one of the most critical controllers of the inflammatory response in glioblastoma multiforme (GBM). In this study, the knockout association of the RELA subunit was examined by expressing some genes connected tothe nuclear factor κB (NF-κB) pathway in sustaining hypoxic circumstances and GBM stem cells (GSCs) properties. A suitable drug is also suggested to target RELA . Targeted deletion of the RELAsubunit in human GBM cells (A172) was performed with CRISP R/Cas9. Nestin (NES) and hypoxia inducible factor 1 alpha (HIF-1α) genes expression levels and induction of apoptosis in transfected and control cells were assessed by Real-time PCR and flow cytometry, respectively. Using the Auto Dock Vina software, a molecular docking study was conducted to find the optimum intermolecular interaction between RELA protein and four potential drugs. Real-time PCR results showed a decrease in the expression of HIF-1α and NES genes in the transfected cell population compared to the control cells (p< 0.0102, p< 0.0012, and P< 0.0442, respectively). Flow cytometry results showed a significantly increased induction of apoptosis in the transfected cells compared to the control cell population. The results of docking revealed that Ecteinascidin-743 has the best intermolecular interaction with RELAprotein. In conclusion, the RELA subunit seems to be one of the factors affecting hypoxia, apoptosis, and change in stemness genes expression levels in GBM. Therefore, it is recommended to knock out the NF-κB signalling pathway or to use Ecteinascidin-743 in future studies.